The Paradox of Tolerance, Freedom of Religion, and Moral Boundaries in Implementation of Human Rights Law - Meliyani Sidiqah (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
The discussion of tolerance and religious freedom in Indonesia reveals a normative paradox: constitutional guarantees of human rights coexist with restrictive practices grounded in majority morality. While religious freedom is constitutionally guaranteed as a fundamental right tied to human dignity, Indonesian legal culture often enforces tolerance in a conditional, passive, or exclusive manner. This paradox shapes the complex interplay among religion, the state, and society, as the collective morality of dominant groups frequently becomes public morality, restricting minority rights. This article seeks to clarify how tolerance for religious freedom is constructed within Indonesian legal culture and to examine the moral boundaries that limit religious freedom. Using a normative juridical approach informed by interdisciplinary human rights law, legal philosophy, and moral philosophy, the research finds that tolerance in Indonesia is primarily passive and legitimized by majority morality. Dominant group values often become public morality without rational evaluation against universal human rights standards, resulting in asymmetric and exclusive restrictions on minorities. This research’s novelty lies in offering a normative framework that treats tolerance as a legal-philosophical issue and proposes reorienting moral boundaries toward universal human rights by strengthening active tolerance and public rationality, ensuring that religious freedom is not only normatively recognized but also meaningfully protected in Indonesia’s democratic and just legal culture.